Synthesis and characterization of zero-valent iron nanoparticles supported on SBA-15 - Felipe Sombra dos Santos; Fernanda Rodrigues Lago; Lídia Yokoyama; Fabiana Valéria Fonseca (Journal of Materials Research and Technology, 2017)
This paper aims to synthesize zero-valent iron nanoparticles (nZVI) supported on SBA-15 nanosilica. The nanosilica generate in the system by polymer reaction with hydrochloric acid under controlled temperature. After, the iron nanomaterial was obtained by sodium borohydride reduction as described in this work. Afterward the synthesis of the nanoparticles contained iron supported on silica SBA-15, the material was characterized by X-ray diffraction, transmission electron microscopy, scanning electron microscopy, zeta potential and X-ray fluorescence spectroscopy. The results indicated that nanomaterial obtained was in nanometric scale, by TEM results, and showing characteristic peaks at EDS results, with 11.9% iron and 14.0% silicon content, respectively, and containing 73.0% and 27.0% of their respective oxides through X-ray fluorescence spectroscopy. The isoelectric potential of the sample was around 2.0, close to the value reported for silica, due to the higher percentage of silica in the sample when compared to iron. The obtained material can be used, for some cases, as an possible alternative, to the Fenton reaction for the degradation of xenobiotic compounds or other applications in the groundwater and wastewater treatments.